HUBUNGAN PERAN GURU PENDIDIKAN AGAMA ISLAM DENGAN RELIGIUSITAS SISWA SEKOLAH MEMENGAH PERTAMA MUHAMMADIYAH WATUKELIR SUKOHARJO - Aini, Bekti Fajar Nur; Anshori, Muhammad Isa; Abbas, Ngatmin (Jurnal Manajemen Pendidikan, 2025)
Islamic Religious Education (PAI) plays a strategic role in shaping students' religious character from an early age. However, declining student religiosity remains a concern across various educational levels, including junior high schools. This study aims to analyze the relationship between the role of Islamic Religious Education teachers and the religiosity of seventh-grade students at SMP Muhammadiyah Watukelir, Sukoharjo. This research employed a quantitative approach using a descriptive correlational method. The sample consisted of 50 students, representing the entire seventh-grade population. The research instrument was a Likert-scale questionnaire that had undergone validity and reliability testing. Data were analyzed using descriptive statistics, normality tests, and Pearson correlation analysis. The results showed that the role of Islamic education teachers was categorized as good (66%), and students’ religiosity was also rated as good (68%). However, the correlation analysis revealed no significant relationship between the teacher's role and student religiosity (r = -0.139; sig. = 0.336). These findings imply the need for stronger collaboration between teachers, parents, and the broader social environment to holistically nurture students’ religiosity. Islamic education teachers are also encouraged to develop more contextual and affective teaching approaches that can deeply engage students' spiritual dimensions.